Levels and Clinical Significances of Glypican-5 in Urine of Type 2 Diabetic Nephropathy Cases (Iranian Journal of Kidney Diseases, 2019)
Introduction. Increased glypican-5 expression in podocytes induces podocyte injury. Glypican-5 is shed into the urine, but its value in predicting progression of diabetic nephropathy (DN) has not been investigated. Methods. Glypican-5 was determined in spot urine from 20 type 2 diabetes mellitus (T2DM) patients, and 37 type 2 DN patients, and 20 healthy controls by enzyme-linked immunosorbent assay. The association of urinary glypican-5 with markers of renal function was evaluated. Results. Urinary glypican-5 was significantly higher in DN patients than in both DM patients and controls. Glypican-5 level was not associated with baseline 24-hour urine protein/albumin excretion, serum creatinine, estimated glomerular filtration rate (eGFR), systolic blood pressure (SBP), or hemoglobin (Hb) A1c values in the DN patients. After 52 weeks follow-up, urinary glypican-5 level was associated with significant increases in urine protein and albumin excretion and a significant decline in eGFR in the DN patients. The decline in eGFR was independent of changes in urine protein and albumin excretion, SBP, or HbA1c. The results indicate that urinary glypican-5 was not only a biomarker but also contributed to the pathogenesis of DN in these patients. Conclusion. Urinary glypican-5 was specifically elevated in type 2 diabetes patients with DN and it was associated with disease progression. Urinary glypican-5 may serve as a useful non-invasive marker for the progression of DN.